High-level chloroquine resistance in Sudanese isolates of Plasmodium falciparum is associated with mutations in the chloroquine resistance transporter gene pfcrt and the multidrug resistance Gene pfmdr1. - Babiker, H; Pringle, S; Abdel-Muhsin, A; Mackinnon, M; Hunt, P; Walliker, D (2001)
Polymorphisms were examined in 2 Plasmodium falciparum genes, as were chloroquine responses of clones and isolates from a village in eastern Sudan. There was a significant association between an allele of the P. falciparum chloroquine resistance transporter gene (pfcrt-T76) and both in vitro and in vivo resistance. There was a less significant association with the multidrug resistance gene pfmdr1-Y86 allele. A significant association between pfmdr1-Y86 and pfcrt-T76 was apparent among resistant isolates, which suggests a joint action of the 2 genes in high-level chloroquine resistance.